Pengembangan Media Pembelajaran "Perubahan Lingkungan Fisik Bumi" Menggunakan Fitur Interaksi Class Point dan Video Edpuzzle di Kelas 5 SD - Silvi Laila Rista Fauziah; Putra Ika Viratama (Aljabar : Jurnal Ilmuan Pendidikan, Matematika dan Kebumian, 2026)
The Integration of technology in the education sector is a crucial strategy for addressing the challenges of the Industrial Revolution 4.0. This study aims to develop and examine the effectiveness of "Physical Changes of the Earth’s Environment" learning media by utilizing the interactive features of the ClassPoint platform and Edpuzzle videos in 5th-grade elementary school. The method employed is library research with a qualitative-descriptive approach, conducted through content analysis of various relevant scientific literatures from the last five years. The research findings indicate that the synergy between ClassPoint and Edpuzzle is capable of transforming abstract science materials into more concrete and engaging content for students. ClassPoint plays a role in creating a participatory digital classroom through various real-time interaction formats, while Edpuzzle reorients video-viewing activities into an active learning process through embedded question features that stimulate critical thinking. Overall, the use of these interactive media has positive implications for the escalation of active participation, concentration, and the depth of students' conceptual understanding. This study concludes that the development of ClassPoint and Edpuzzle-based learning innovations is an effective and relevant strategic step in improving the quality standards of science education in elementary schools.